La indagación como estrategia didáctica para el aprendizaje de zoología de los invertebrados para los estudiantes de quinto semestre de la carrera de Biología Química y Laboratorio período septiembre 2014-marzo 2015 - Ramírez Reinoso, Olga Verónica (2016)
This research was conducted at the National University of Chimborazo in the city of Riobamba, aimed at students of fifth semester of the School of Chemical Biology Laboratory, because he was found in students performing poorly in the subject of Zoology Invertebrates. The aim of the research was to apply the inquiry as a teaching strategy for learning Invertebrate Zoology aimed at students of fifth semester of the School of Chemical Biology and Laboratory period September 2014 to March 2015, the study group was 9 students Fifth Semester, whom questionnaires were applied with closed, open, mixed questions. 67% of students surveyed say they almost always INQUIRY helps the organization of work, so the hypothesis was also found to accept that the inquiry as a teaching strategy, facilitates the learning of Invertebrate Zoology. At the conclusion it is important to highlight the inquiry as a teaching strategy for learning Invertebrate Zoology as it allowed, create, classify and publish the information necessary to improve the learning process of students. So teachers career and Chemical Biology Laboratory is also recommended to use the information available in the Learning Guide "The world of invertebrates" for learning Zoology of invertebrates.